Validação de vídeo educativo sobre cuidados paliativos para cuidadores de idosos - Xavier, Ticianne Alves (2023)
Introduction: Population aging has been noticed in developing countries for a few decades. As a result of this phenomenon, everything related to human aging assumes a prominent role. The significant increase in people over 60 years of age raises another concern exponentially: who will take care of this elderly person? With the increase in the prevalence of chronic and disabling diseases, associated with the growing demand from elderly patients, who seek health institutions and are referred to the hospital environment, there is a greater need for services that offer palliative care, with there still being a need for elderly caregivers. Objective: Validate educational material on palliative care for caregivers of elderly people at a teaching hospital. Method: This is a methodological study, which aimed to develop an educational video aimed at caregivers of elderly people undergoing internal palliative care in the Medical Clinic of a university hospital. The study was developed in three stages, namely: integrative review of the literature on the topic under study to support the preparation of the script, narration and creation of illustrations for the proposed video; video development and content validation by expert judges. Results and discussion: The video validation process involved the participation of 16 content judges, all health professionals with experience in palliative and/or elderly care. The video created included 18 scenes that addressed the concept of palliative care, the importance of the caregiver and care for the most prevalent symptoms faced by patients. The content judges' assessment was based on a content validation index, which allowed quantifying the suitability of the video in relation to seven aspects evaluated, such as: objective, content, language, relevance, illustration, layout and motivation. In general, the video obtained above average scores for most of the items evaluated, indicating good quality in the content covered, with a final validation index of 0.96. Final considerations: The use of educational videos as a form of training and guidance for caregivers of elderly people can be an effective and accessible alternative. By validating the video, we sought to ensure that the content was correctly transmitted and understood, contributing to the provision of quality care to elderly patients in palliative care.